2011
DOI: 10.1002/ptr.3246
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic activity of a supercritical carbon dioxide extract of Souroubea sympetala (Marcgraviaceae)

Abstract: The purpose of this work was to develop an extraction technique to yield a betulinic acid-(BA) enriched extract of the traditional anti-anxiety plant Souroubea sympetala Gilg (Marcgraviaceae). Five extraction techniques were compared: supercritical carbon dioxide extraction (SCE), conventional solvent extraction with ethyl acetate (EtOAc), accelerated solvent extraction (ASE), ultrasonic assisted extraction (UAE) and soxhlet extraction (Sox). The EtOAc and SCE extraction methods resulted in BA-enriched extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…In both, SSBB and PTB the betulinic acid (BA) is considered to be the major active component. Both species were analysed for BA content by HPLC/MS methods as previously described [5]. BA possesses anxiolytic properties at low doses (1 mg/kg) [6] and has potential benefi ts in canc er therapy [7,8] reduction of HIV replication [9,10], infl ammation [11] and bacterial infections at much higher doses (50-500 mg/kg) [12].…”
Section: Preparation and Characterization Of Ssbb And Ptbmentioning
confidence: 99%
“…In both, SSBB and PTB the betulinic acid (BA) is considered to be the major active component. Both species were analysed for BA content by HPLC/MS methods as previously described [5]. BA possesses anxiolytic properties at low doses (1 mg/kg) [6] and has potential benefi ts in canc er therapy [7,8] reduction of HIV replication [9,10], infl ammation [11] and bacterial infections at much higher doses (50-500 mg/kg) [12].…”
Section: Preparation and Characterization Of Ssbb And Ptbmentioning
confidence: 99%
“…Therefore, new environmentally and human-friendly technologies are badly needed. Although application of supercritical carbon dioxide technique reduces the use of organic solvents in BA extraction (Mullally et al, 2011;Patinha et al, 2013), the high pressure conditions and high costs limit its up-scale potential.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the species was included in the Norantea genus (Giraldo-Cañas, 2004), but it now belongs to the Schwartzia genus. Pharmacological studies with some species of the Marcgraviaceae family indicate antifungal (Jones et al, 2000) and anxiolytic activities (Mullally et al, 2011). Studies investigating the medicinal potential of S. brasiliensis also reported antibacterial activities (Mello et al, 2014), and Agripino et al (2004) showed that ethanol extracts of stems of S. brasiliensis could protect against DNA damage.…”
Section: Introductionmentioning
confidence: 99%